1998
DOI: 10.1111/j.1574-6968.1998.tb13105.x
|View full text |Cite
|
Sign up to set email alerts
|

Host cell surface sialic acid residues are involved on the process of penetration ofToxoplasma gondiiinto mammalian cells

Abstract: Tachyzoites of Toxoplasma gondii are able to infect several cell types tested (wild-type chinese hamster ovary (CHO) cells and glycosylation mutants, Vero and LLCMK2 cells). However, the extent of infection varied. Mutant cells which present few or no surface-exposed sialic acid residues were infected to a lower extent. Similar results were obtained if sialic acid residues were removed by previous neuraminidase treatment. Addition of sialic acid residues to surface-exposed glycoconjugates using fetuin as a sia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Some bacterial pathogens exploit this interaction by either scavenging sialic acid to coat their surfaces or synthesizing their own to recruit FH and thereby protect their surface from complement attack (64)(65)(66). Several studies have demonstrated that T. gondii possess a lectin like activity associated with its ability to interact with host SPGs (67,68) and sialic acid (69,70). It has been reported that C4BP also contains a binding domain for heparin (63).…”
Section: Discussionmentioning
confidence: 99%
“…Some bacterial pathogens exploit this interaction by either scavenging sialic acid to coat their surfaces or synthesizing their own to recruit FH and thereby protect their surface from complement attack (64)(65)(66). Several studies have demonstrated that T. gondii possess a lectin like activity associated with its ability to interact with host SPGs (67,68) and sialic acid (69,70). It has been reported that C4BP also contains a binding domain for heparin (63).…”
Section: Discussionmentioning
confidence: 99%
“…Tachyzoites bind vascular endothelium in intact human retina under flow conditions (Chipps et al, 2006), and the binding-invasion step occurs relatively quickly for human retinal endothelial cells (Zamora et al, 2008). Sulfated proteoglycans have been implicated as host receptors on non-endothelial cells (Carruthers et al, 2000; Monteiro et al, 1998; Ortega-Barria and Boothroyd, 1999). In this respect, results of our gene expression microarray study might be relevant, showing that human retinal endothelial cells express relatively high levels of multiple sulfotransferases.…”
Section: Infectious Posterior Uveitismentioning
confidence: 99%
“…There are two known factors in the host cell invasion by T. gondii, including parasite-derived proteins and receptors on the host cell surface. It is known that abundant carbohydrate molecules on host cell surface, such as sialic acid, heparan sulfate and chondroitin sulfate, are receptors for T. gondii invasion (Monteiro et al, 1998;Carruthers et al, 2000;Baba et al, 2015), but the parasite ligands interacting with these receptors have not been well-characterized.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, merozoites of Plasmodium falciparum recognize and interact with N-acetylneuraminic acid residues on red blood cell (RBC) for erythrocyte invasion (Malpede et al, 2013), and Trypanosoma cruzi can invade macrophage by parasite trans-sialidase transfering sialic-acid residues from host glycoconjugates to parasite mucins (Morrot, 2013). It has been reported that the infection rate of T. gondii for the sialic acid-lacking mutant host cells was lower than that for wild type cells (Monteiro et al, 1998). Also, it was observed about 90% reduction of invasion efficiency when N-acetylneuraminic acid (NANA) was used as a competitor or when host cells were treated with neuraminidase (Blumenschein et al, 2007;Friedrich et al, 2010).…”
Section: Introductionmentioning
confidence: 99%